Exploring yield growth to 2050: Updating yield growth parameters in IMPACT - Orozco Ceron, Esperanza; Rivera Vasco, Tatiana Carolina; Petsakos, Athanasios; Suarez, Victor; Hareau, Guy; Enahoro, Dolapo; Pede, Valerien; Alene, Arega; Andrade Lopez, Robert Santiago (2024)
This tool has been developed under the auspices of the CGIAR Initiative on Foresight & Metrics. Its objective is to support the update of exogenous yield growth parameters to 2050 in the International Model for Policy Analysis of Agricultural Commodities and Trade (IMPACT) of the International Food Policy Research Institute (IFPRI). These exogenous yield growth parameters, commonly referred to as "Intrinsic Productivity growth Rates" (IPRs), represent a component of agricultural productivity that cannot be attributed to price effects, climate and water shocks - elements which are explicitly captured by IMPACT (for example new technologies, better management, improved input use efficiency, etc.) Estimating IPRs to 2050 can be better understood as an exercise to derive future yield growth parameters from an informed extrapolation of observed past trends.